Reproductive and endocrine effects of artemisinin, piperaquine, and artemisinin-piperaquine combination in rats - Xiaobo Li; Yueming Yuan; Yingyi Chen; Li Ru; Zheng Yuan; Zhiyong Xu; Qin Xu; Jianping Song; Guoming Li; Changsheng Deng (BMC, 2022)
Abstract Background: The WHO recommends artemisinin-based combination regimens for uncomplicated Plasmodium falciparum malaria. One such combination is artemisinin-piperaquine tablets (ATQ). ATQ has outstanding advantages in anti-malarial, such as good efficacy, fewer side effects, easy promotion and application in deprived regions. However, the data about the reproductive and endocrine toxicity of ATQ remains insufficient. Thus, we assessed the potential effects of ATQ and its individual components artemisinin (ART) and piperaquine (PQ) on the reproductive and endocrine systems in Wistar rats. Methods: The unfertilized female rats were intragastric administrated with ATQ (20, 40, and 80 mg/kg), PQ (15, 30, and 60 mg/kg), ART (2.5, 5, and 10 mg/kg), or water (control) for 14 days, respectively. The estrous cycle and serum levels of estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), prostaglandin (PG), and adrenocorticotropic hormone (ACTH) were determined. The weights of the kidney, adrenal gland, uterus, and ovaries were measured. The histopathological examinations of the adrenal gland, ovary, uterus, and mammary gland were performed. Results: Compared with the control group, there were no significant differences in the examined items of female rats in the ART groups, including general observation, estrous cycle, hormonal level, organ weight, and histopathological examination. The estrous cycle of female rats was disrupted within 4-7 days after ATQ or PQ administration, and then in a persistent dioestrus phase. At the end of administration, ATQ and PQ at three doses induced decreased PG, increased ACTH, increased adrenal weight and size, and pathological lesions in the adrenal gland and ovary, including vasodilation and hyperemia in the adrenal cortex and medulla as well as hyperplasia and vacuolar degeneration, ovarian corpus luteum surface hyperemia, numerous but small corpus luteum, and disordered follicle development. But the serum levels of E2, FSH, LH, and PRL did not change obviously. These adverse effects in ATQ or PQ treated rats could not completely disappear after 21 days of recovery. Conclusion: Based on the results of this study, ART had no obvious reproductive and endocrine effects on female rats, while ATQ and PQ caused adrenal hyperplasia, increased ACTH, decreased PG, blocked estrus, corpus luteum surface hyperemia, and disrupted follicle development in female rats. These events suggest that ATQ and PQ may interfere with the female reproductive and endocrine systems, potentially reducing fertility.